2022
DOI: 10.1177/09727531211070528
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Heat Shock Proteins in Neurodegeneration: Possible Therapeutical Targets

Abstract: Human neurodegenerative diseases occur as a result of various factors. Regardless of the variety in the etiology of development, many of these diseases are characterized by the accumulation of pathological, misfolded proteins; hence, such diseases are considered as proteinopathies. While plenty of research study has been conducted in order to identify the pathophysiology of these proteinopathies, there is still a lack of understanding in terms of potential therapeutic targets. Molecular chaperones present the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 115 publications
0
14
0
Order By: Relevance
“…Considering the functional significance of these Hsp70 chaperones in the proteotoxic stress response, their targeting to reverse and combat protein aggregation-mediated neurodegeneration is potentially an excellent therapeutic approach. Hsp70 up-regulation and modulation are widely tested in treating many neurodegenerative diseases [ 18 , 19 , 56 , 57 ]. Chaperones, in combination, are more potent in eliciting preventive responses than individual entities [ 58 ].…”
Section: Discussionmentioning
confidence: 99%
“…Considering the functional significance of these Hsp70 chaperones in the proteotoxic stress response, their targeting to reverse and combat protein aggregation-mediated neurodegeneration is potentially an excellent therapeutic approach. Hsp70 up-regulation and modulation are widely tested in treating many neurodegenerative diseases [ 18 , 19 , 56 , 57 ]. Chaperones, in combination, are more potent in eliciting preventive responses than individual entities [ 58 ].…”
Section: Discussionmentioning
confidence: 99%
“…HSPs have recently become a focus of research in neurodegenerative diseases (such as AD, Parkinson's disease, polyglutamine (polyQ) disease, Amyotrophic lateral sclerosis, Huntington's, and many others) because the pathogenesis of these diseases is highlighted by the intracellular proteins aberrant folding and inclusion body formation. 282 HSPs serve as protein‐folding machinery and work together with UPS to assist in removing aberrant proteins, exert antiapoptotic effects, and maintain the dynamic homeostasis of dopaminergic neurons against stress conditions such as oxidative damage. Dysfunction of HSPs, including HSP90, HSP70, and HSP27, may contribute to the pathogenesis of Parkinson's disease as a study showed, suggesting that HSPs may come to be potential therapeutic targets for neurodegenerative disorders such as PD.…”
Section: Hspss As Potential Therapeutic Targetsmentioning
confidence: 99%
“…355 Moreover, many studies shown that HSP70 may solubilize α-syn and promote the degradation of its insoluble forms via chaperone-mediated autophagy and the proteasome pathway in PD. 281,282 In addition, other studies suggested that HSP70 plays a role in neuroprotective in diseases that affect CNS and showed promising outcome in reducing the loss of neuron cells. 356 Therefore, future strategies for developing treatments for neurodegenerative diseases through targeting HSP70 can be proposed.…”
Section: Hsps As Targets In Neurodegeneration Diseasesmentioning
confidence: 99%
See 1 more Smart Citation
“…In general, the ability of the chaperone machine to bind Aβ and prevent the formation of amyloid aggregates and their toxicity in vitro is well-established [ 102 , 103 ], but experimental confirmation of this hypothesis in vivo has not yet been presented.…”
Section: Aβ and Its Protein Interactorsmentioning
confidence: 99%